The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.scr.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

MYB fusions and CD markers as tools for authentication and purification of cancer stem cells from salivary adenoid cystic carcinoma

Abstract: Cancer stem cells (CSC) are considered the major cause of aggressive tumor behavior, recurrence, metastases, and resistance to radiation, making them an attractive therapeutic target. However, isolation of CSC from tumor tissue and their characterization are challenging due to uncertainty about their molecular markers and conditions for their propagation. Adenoid cystic carcinoma (ACC), which arises predominantly in the salivary glands, is a slow-growing but relentless tumor that frequently invades nerves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
(61 reference statements)
2
16
1
Order By: Relevance
“…Many previous studies showed that Notch1 pathway plays a crucial role in CSCs maintaining stemness. 20 22 Despite the opposite roles of Notch1 signaling in CD24 expression in breast cancer cells and melanoma cells, the results of both our study and So et al’s study confirmed that Notch1 signaling maintains the tumorigenic ability of CSCs.…”
Section: Discussionsupporting
confidence: 76%
“…Many previous studies showed that Notch1 pathway plays a crucial role in CSCs maintaining stemness. 20 22 Despite the opposite roles of Notch1 signaling in CD24 expression in breast cancer cells and melanoma cells, the results of both our study and So et al’s study confirmed that Notch1 signaling maintains the tumorigenic ability of CSCs.…”
Section: Discussionsupporting
confidence: 76%
“…SOX-10 was all positive in our series of cases. Although SOX-10 is a marker for sero-mucinous differentiation (23), our findings demonstrated that it is not a specific marker for AdCC.…”
Section: Discussioncontrasting
confidence: 69%
“…Capturing signaling states by measuring protein phosphorylation in various cell subsets can also define or reveal their phenotype. For example, detection of WNT/β‐catenin and STAT3 signaling in a CD133 + cell line derived from a salivary adenoid cystic carcinoma by mass cytometry helped characterize these cells as cancer stem cell‐like . We recently identified novel tumor cell subsets based on basal signaling profile in glioblastoma .…”
Section: Mass Cytometry To Reveal Cancer Biology Beyond Genomicsmentioning
confidence: 99%